Effect of Cervical Collar Removal on the Fracture Load of Anterior Zirconia Crowns - Campos, Fernanda [UNESP]; Cardoso, Mayra; Melo, Renata Marques de [UNESP]; Bottino, Marco Antonio [UNESP]; Souza, Rodrigo O. A. (Quintessence Publishing Co Inc, 2017)
The objective of this study was to assess the influence of the extension of collar and fatigue cycling on the fracture load of anterior zirconia crowns. A total of 60 anterior full-crown preparations (central incisor) were machined in glass fiberfilled epoxy resin. Zirconia copings were designed and milled using computeraided design/ computer-assisted manufacture (thickness: buccal = 0.62 mm, lingual = 0.65 mm, incisal = 0.72 mm). The cervical collars (occlusogingival height = 0.8 mm, buccolingual width = 1.0 mm) were totally or partially (buccal face) removed for modified copings. They were randomly allocated to six groups according to the type of cervical collar design and the presence (or not) of fatigue cycling (n = 10). The veneering ceramic layer was pressed, and the crowns were cemented with resin cement. The samples were tested until fracture in a universal testing machine and analyzed by stereomicroscopy. Data were statistically analyzed by two-way analysis of variance and Tukey test (5%). Removal of the cervical collar significantly affected the fracture strength of zirconia crowns (P =.000), whereas fatigue cycling did not (P =.428). The mean failure load was lower in the groups with no collar. The most frequent failure modes were cracking of the veneer porcelain in collarless crowns and catastrophic failure in the others. The authors concluded that removal of the vestibular collar of zirconia copings in anterior crowns does not reduce the fracture load of the crowns. However, removal of the entire collar reduces the fracture load and cannot be recommended.